Buried graphene heterostructures for electrostatic doping of low-dimensional materials. (25th June 2023) - Gumprich, A; Liedtke, J; Beck, S; Chirca, I; Potočnik, T; Alexander-Webber, J A; Hofmann, S; Tappertzhofen, S
Abstract: The fabrication and characterization of steep slope transistor devices based on low-dimensional materials requires precise electrostatic doping profiles with steep spatial gradients in order to maintain maximum control over the channel. In this proof-of-concept study we present a versatile graphene heterostructure platform with three buried individually addressable gate electrodes. The platform is based on a vertical stack of embedded titanium and graphene separated by an intermediate oxide to provide an almost planar surface. We demonstrate the functionality and advantages of the platform by exploring transfer and output characteristics at different temperatures of carbon nanotube field-effect transistors with different electrostatic doping configurations. Furthermore, we back up the concept with finite element simulations to investigate the surface potential. The presented heterostructure is an ideal platform for analysis of electrostatic doping of low-dimensional materials for novel low-power transistor devices.